Recent intensified riverine CO2 emission across the Northern Hemisphere permafrost region - Cuicui Mu; Kun Li; Shaoda Liu; Yuguo Wei; Mei Mu; Xuexue Shang; Fumei Liu; Chunling Zhang; Hebin Liu; Tanguang Gao; Chunlin Song; Liwei Zhang; et al. (Nature Communications)
Abstract Global warming causes permafrost thawing, transferring large amounts of soil carbon into rivers, which inevitably accelerates riverine CO2 release. However, temporally and spatially explicit variations of riverine CO2 emissions remain unclear, limiting the assessment of land carbon-climate feedback. Using new and published 5685 riverine CO2 partial pressure data in the Arctic and Tibetan Plateau, we show that current riverine CO2 emission across the Northern Hemisphere permafrost zone is 200 ± 15 Tg C yr⁻1. The emission offsets 28.1 ± 2.1% of the land carbon uptake in the Northern Hemisphere permafrost zone, with large regional variability of 13.1 to 63.1%. Our findings suggest that CO2 emissions increased at a rate of 0.42 ± 0.16 Tg C yr⁻1 during 2000 to 2020, and this is primarily driven by increased precipitation and accelerated permafrost thawing under climate change. This study highlights increased riverine carbon emission and strengthening of the permafrost carbon feedback to climate after incorporating carbon release from rivers.